Systems Analysis of Protein Fatty Acylation in Herpes Simplex Virus-Infected Cells Using Chemical Proteomics - Serwa, Remigiusz A. (Chem Biol, 2015)
Protein fatty acylation regulates diverse aspects of cellular function and organization and plays a key role in host immune responses to infection. Acylation also modulates the function and localization of virus-encoded proteins. Here, we employ chemical proteomics tools, bio-orthogonal probes, and capture reagents to study myristoylation and palmitoylation during infection with herpes simplex virus (HSV). Using in-gel fluorescence imaging and quantitative mass spectrometry, we demonstrate a generalized reduction in myristoylation of host proteins, whereas palmitoylation of host proteins, including regulators of interferon and tetraspanin family proteins, was selectively repressed. Furthermore, we found that a significant fraction of the viral proteome undergoes palmitoylation; we identified a number of virus membrane glycoproteins, structural proteins, and kinases. Taken together, our results provide broad oversight of protein acylation during HSV infection, a roadmap for similar analysis in other systems, and a resource with which to pursue specific analysis of systems and functions.